Nanobody-enabled monitoring of kappa opioid receptor states - Tao Che (Nature Portfolio, 2020)
Recent studies revealed that G protein-coupled receptors rapidly interconvert between multiple states. Here, authors use the kappa opioid receptor (KOR) and show how two state-dependent nanobodies provide real-time reporting of ligand stabilized states with KOR and other GPCRs.